Evaluation of Sports and Health Physical Education Learning in Vocational High Schools in Kendal Regency During the Covid-19 Pandemic (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The objective of this study was to investigate the Context, Input, Process, and Products of PJOK learning at Vocational Schools in Kendal Regency during the Covid-19 pandemic. The CIPP model was used in this study as an evaluation model. The participants in this study were school principals, PJOK teachers, and students from Vocational Schools in Kendal Regency. Purposive sampling was used, with information on 7 school principals, 7 PJOK teachers, and 105 students. Techniques for gathering data included observation, interviews, questionnaires, and documentation. The descriptive quantitative and qualitative data analysis technique was used in this study. The evaluation of the implementation of PJOK learning at Vocational Schools in Kendal Regency during the Covid-19 pandemic was 3,044 in the good category, according to the results. The following outcomes were obtained based on each evaluation component. (1) During the Covid-19 pandemic, the context of evaluating the implementation of PJOK learning at Vocational Schools in Kendal Regency was 3.1 in the good category. The Physical Education learning philosophy indicator was 3.11, and the Physical Education learning objective was 3.09, both of which were good. (2) The program input for evaluating the implementation of PJOK learning at Vocational Schools in Kendal Regency during the Covid-19 pandemic, totaling 3,016, was in the good category. The indicator for teacher profile was 2.79 in the good category, the indicator for student profile was 3.17 in the good category, and the indicator for learning facilities and infrastructure was 3.17 in the good category. During the Covid-19 pandemic, the input for evaluating the implementation of learning at Vocational Schools throughout Kendal Regency was 3.016 in the good category. (3) The process evaluation of the program for evaluating the implementation of PJOK learning at Vocational Schools in Kendal Regency during the Covid-19 pandemic, with a score of 3.04, was good. (4) The program for evaluating the implementation of PJOK learning at Vocational Schools in Kendal Regency during the Covid-19 pandemic received a good rating of 3.18. The evaluation of learning outcomes was 3.18 in the good category, and the evaluation of learning processes was 3.18 in the good category.